Effect of Sociodemographic Factors on the Risk of Postpartum Depression during the Covid-19: Evidence from Tarakan - Febrianti, Selvia; Ariyanti, Ririn; Jalilah, Nurul Hidayatun (JURNAL INFO KESEHATAN, 2023)
Social and environmental factors can have an impact on a mother's mental health, especially during a pandemic. Financial stress and the social environment can exacerbate postpartum depression. Postpartum depression is one of the mental health consequences. Postpartum depression is similar to other types of depression, but it occurs as a result of physical and social changes caused by the process of giving birth and raising a child. The objective of this study was to identify the sociodemographic factors that influence the risk of postpartum depression in Tarakan during the Covid-19 pandemic. It was a cross-sectional study conducted in Tarakan's North Tarakan District from August to October 2021. The study included 150 postpartum mothers. In this study, simple random sampling was used. The dependent variable of this study was postpartum depression and independent variables were age, education, income, parity, occupation, and support. Data collection employed questionnaires and logistic regression data analysis with the Stata 13 program. The risk of postpartum depression increased with multiparity (95%CI: 0.11-1.78); p = 0.026), and less income (< minimum wage) (95%CI: 0.01-1.48); p=0.045). The risk of postpartum depression decreased with age (<35 years old) (95%CI: (-2.00) - (-0.25)); p= 0.011), occupation (95%CI: (-1.60) – (-0.07)); p= 0.032), support (95%CI: (-1.76) – (-0.10)); p= 0.028), higher education (95%CI: (-1.22) – 0.24); p= 0.190). Postpartum depression risk increases with multiparity and lower income. With normal age, occupation, support, and education, the risk of postpartum depression decreased.